CAMELS Rating System Analysis of Bangladesh Bank in Accordance with BRAC Bank Limited - Datta, Rahul Kanti (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.